Adhesive sheet, optical member with adhesive layer, and image display device
By controlling the dielectric constant and adhesive force in the adhesive layer, combined with specific adhesive compositions and process treatment, the problem of reduced polarity and insufficient drop impact resistance on the surface of the adhesive sheet is solved, and noise reduction is achieved and enhance adhesion effect.
Patent Information
- Application Number
- CN202410787489.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-19
- Filing Date
- 2024-06-18
- Publication Date
- 2024-12-20
AI Technical Summary
After the low dielectric constant treatment of the conventional adhesive sheet, the polarity of the surface of the adhesive sheet decreases, resulting in insufficient adhesion of the interface with the adherent object, especially insufficient drop impact resistance.
By controlling the dielectric constant to be less than 4 in the adhesive layer, the glass adhesion under specific conditions reaches 10N/20mm, and no peeling occurs during the drop-resistant impact test, combined with a specific adhesive combination The substance and process treatment, such as using acrylic polymers and hydrogenated polyolefin resins, form an adhesive layer with low dielectric constant and high adhesion.
It realizes noise reduction, enhances adhesion, and has good drop impact resistance, and is suitable for optical component bonding of image display devices and touch panels.
Smart Images

Figure BDA0004899003510000121 
Figure BDA0004899003510000211 
Figure HDA0004899003520000011
Abstract
Description
Technical Field
[0001] The present invention relates to a pressure-sensitive adhesive sheet, a pressure-sensitive adhesive layer-attached optical member, and an image display device. Background Art
[0002] In recent years, image display devices such as liquid crystal displays (LCDs) and organic electroluminescent displays (OLEDs), and touch panels in which touch sensors are assembled in these image display devices are widely used in various fields. Such image display devices and touch panels have a structure in which various optical components such as a polarizing film, a phase difference film, an optical compensation film, a touch sensor film, and a cover film are stacked on the image display panel. Adhesive sheets having an adhesive layer are used for bonding these optical components. For example, transparent adhesive sheets are used for bonding various optical components in image display devices (for example, refer to Patent Documents 1 to 3).
[0003] In particular, a pressure-sensitive adhesive sheet used in a touch panel is required to have a low dielectric constant in order to reduce erroneous operation due to the generation of noise in addition to the above.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2003-238915
[0007] Patent Document 2: Japanese Patent Application Publication No. 2003-342542
[0008] Patent Document 3: Japanese Patent Application Publication No. 2004-231723 Summary of the invention
[0009] Problems to be solved by the invention
[0010] However, when a conventional PSA sheet is subjected to a dielectric constant lowering treatment, the polarity of the PSA sheet surface decreases, and thus the adhesion at the interface with the adherend may become insufficient, and in particular, there is a problem that the drop impact resistance becomes insufficient.
[0011] Therefore, the present invention has been conceived based on such circumstances, and an object of the present invention is to provide a PSA sheet that reduces noise by lowering the dielectric constant, has sufficient adhesive strength to an adherend, and also has drop impact resistance.
[0012] Means used to solve problems
[0013] The present inventors have conducted intensive research to achieve the above-mentioned purpose, and found that if there is an adhesive layer, the adhesive layer does not peel off in a specific drop impact resistance test, the dielectric constant at a frequency of 100 kHz is less than 4, and the glass bonding strength of at least one surface under the conditions of a peeling angle of 180° and a pulling speed of 300 mm / min is greater than 10 N / 20 mm, then the noise can be reduced by lowering the dielectric constant, the adhesive strength to the adherend is sufficient, and the adhesive has drop impact resistance.
[0014] That is, the present invention provides an adhesive sheet, which has an adhesive layer, the adhesive layer does not peel off in the following drop impact resistance test, the dielectric constant of the adhesive layer at a frequency of 100 kHz is 4 or less, and the glass bonding strength of at least one surface of the adhesive layer under the conditions of a peeling angle of 180° and a pulling speed of 300 mm / min is 10 N or more / 20 mm, and the adhesive sheet is used for optical components.
[0015] <Drop impact resistance test>
[0016] A first glass plate (length 100 mm × width 75 mm, thickness 500 μm), the adhesive layer (length 75 mm × width 45 mm), a printed layer (thickness 30 μm) formed within a range of 15 mm inside the entire end edge of the second glass plate, and the second glass plate (length 100 mm × width 50 mm, thickness 500 μm) are stacked in sequence, and heat treated at 50°C, 0.5 MPa, and 30 minutes to produce a joint body; in a state where only the protrusions at both ends of the first glass plate in the width direction are supported by a support platform and the second glass plate is not in contact with the support platform, the joint body is set on a support platform in a manner such that the first glass plate is located on the upper side of the joint body, a metal ball with a mass of 15 g is dropped from a height of 300 mm toward the first glass plate, and it is confirmed whether there is peeling between the adhesive layer and the first glass plate or between the adhesive layer and the printed layer at this time.
[0017] The adhesive layer does not peel off even in the drop impact resistance test, and has a glass bonding strength of 10 N or more / 20 mm under the conditions of a peeling angle of 180° and a pulling speed of 300 mm / min, so that it has sufficient bonding strength and can exert drop impact resistance. In addition, the dielectric constant at a frequency of 100 kHz is 4 or less, which can reduce noise.
[0018] The pressure-sensitive adhesive layer preferably does not peel off even when left at 80° C. for one week after the drop impact resistance test. With the above configuration, the pressure-sensitive adhesive layer can be suitably used even under high-temperature usage conditions.
[0019] The present invention also provides an optical member with a pressure-sensitive adhesive layer, wherein the pressure-sensitive adhesive sheet is bonded to at least one surface of the optical member.
[0020] The present invention also provides an image display device including the pressure-sensitive adhesive layer-attached optical member.
[0021] Moreover, this invention provides the touch panel which has the said pressure-sensitive adhesive layer-attached optical member.
[0022] Effects of the Invention
[0023] The pressure-sensitive adhesive sheet of the present invention reduces noise by lowering the dielectric constant, has sufficient adhesive strength, and has drop impact resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram showing a specific example of a preferred embodiment of the pressure-sensitive adhesive sheet of the present invention.
[0025] Figure 2 It is a schematic diagram which shows the specific example of the preferable aspect of the optical member with a pressure-sensitive adhesive layer of this invention.
[0026] Figure 3 It is a schematic diagram showing a specific example of a preferred embodiment of the image display device of the present invention.
[0027] Figure 4 It is a schematic diagram showing a specific example of a preferred embodiment of the touch panel of the present invention.
[0028] Description of symbols
[0029] 1 Adhesive sheet
[0030] 10 Adhesive layer
[0031] 11, 12 Release liner
[0032] 2A Optical member with adhesive layer
[0033] 2B Touch sensor film with adhesive layer
[0034] 20 Adhesive layer
[0035] 21 Optical components
[0036] 22 Release liner
[0037] 23 Touch sensor film
[0038] 24 Metal wiring
[0039] 3 Image display device
[0040] 30, 31 adhesive layer
[0041] 32 Image display panel
[0042] 33 Polarizing film
[0043] 34 transparent substrate
[0044] 4 Touch Panel
[0045] 40, 41 adhesive layer
[0046] 42 Image display panel
[0047] 43 Touch sensor film
[0048] 44 transparent substrate
[0049] 45 Metal wiring DETAILED DESCRIPTION
[0050] [Adhesive sheet]
[0051] The adhesive sheet of the present invention comprises an adhesive layer, wherein the adhesive layer does not peel off from an adherend in the following drop impact resistance test, the dielectric constant of the adhesive layer at a frequency of 100 kHz is 4 or less, and the glass bonding strength of at least one surface of the adhesive layer under the conditions of a peeling angle of 180° and a pulling speed of 300 mm / min is 10 N or more / 20 mm, and the adhesive sheet is used for optical components.
[0052] <Drop impact resistance test>
[0053] A first glass plate (length 100 mm × width 75 mm, thickness 500 μm), the adhesive layer (length 75 mm × width 45 mm), a printed layer (thickness 30 μm) formed within a range of 15 mm inside the entire end edge of the second glass plate, and the second glass plate (length 100 mm × width 50 mm, thickness 500 μm) are stacked in sequence, and heat treated at 50°C, 0.5 MPa, and 30 minutes to produce a joint body; in a state where only the protrusions at both ends of the first glass plate in the width direction are supported by a support platform and the second glass plate is not in contact with the support platform, the joint body is set on a support platform in a manner such that the first glass plate is located on the upper side of the joint body, a metal ball with a mass of 15 g is dropped from a height of 300 mm toward the first glass plate, and it is confirmed whether there is peeling between the adhesive layer and the first glass plate or between the adhesive layer and the printed layer at this time.
[0054] The adhesive sheet is used in image display devices such as liquid crystal displays (LCDs) and organic electroluminescent displays (OLEDs), and in touch panels in which touch sensors are assembled in these image display devices, to adhere optical components such as polarizing films, phase difference films, optical compensation films, touch sensor films, and cover films to image display panels, or to adhere these optical components to each other.
[0055] It should be noted that, in this specification, when referred to as an "image display device", this includes a "touch panel" unless otherwise specified.
[0056] The above-mentioned adhesive sheet can be a double-sided adhesive sheet with both sides being the adhesive layer surface, or can be a single-sided adhesive sheet with only one side being the adhesive layer surface. Wherein, from the viewpoint of laminating 2 members to each other, it is preferably a double-sided adhesive sheet. It should be noted that when referred to as "adhesive sheet" in this specification, it also includes a tape-shaped adhesive sheet, i.e. "adhesive tape". In addition, in this specification, the adhesive layer surface is sometimes referred to as "adhesive face".
[0057] (Adhesive layer)
[0058] The above-mentioned adhesive layer is not particularly limited. From the viewpoint of preventing malfunction of the touch panel having the above-mentioned adhesive layer, the dielectric constant is preferably controlled to be relatively low. The dielectric constant of the above-mentioned adhesive layer at 20°C and a frequency of 100kHz is 4 or less, preferably 3.9 or less, and more preferably 3.8 or less. The lower limit of the dielectric constant at a frequency of 100kHz is not particularly limited, and is preferably 1.5 or more, more preferably 1.8 or more, and further preferably 2.0 or more. It should be noted that the lower limit of the dielectric constant at a frequency of 100kHz can be 2.1 or more, 2.2 or more, 2.3 or more, 2.4 or more, or 2.5 or more. By having the lower limit of the above-mentioned dielectric constant be 1.5 or more, the adhesive layer is easy to exert adhesion. It should be noted that the above-mentioned dielectric constant is measured according to JIS K6911.
[0059] At least one surface of the above-mentioned adhesive layer has an adhesion to the glass plate of 10N or more / 20mm measured under the conditions of a peeling angle of 180° and a pulling speed of 300mm / min using a tensile testing machine under an environment of 23°C and 50% RH, and can be easily bonded. In addition, it is preferably 12N or more / 20mm, and more preferably 14N or more / 20mm. As an upper limit value, there is no particular restriction, for example, it can be 30N or less / 20mm. In addition, from the viewpoint of reworkability, it is preferably 24N or less / 20mm, more preferably 22N or less / 20mm, and particularly preferably 20N or less / 20mm. It should be noted that when the above-mentioned adhesive layer is used as a double-sided adhesive sheet, it is preferred that the adhesion of both surfaces is within the above range.
[0060] The adhesive layer does not peel off even in the drop impact resistance test, preferably does not peel off even in the drop impact resistance test at a height of 400 mm. An adhesive layer that does not peel off from an adherend in the drop impact resistance test has good drop impact resistance.
[0061] Furthermore, it is preferred that the adhesive layer does not peel off when left at 80° C. for one week after the drop impact resistance test. A pressure-sensitive adhesive layer having such properties can be suitably used even under high-temperature usage conditions.
[0062] Furthermore, it is preferred that the adhesive layer does not peel off when left at -10°C for one week after the drop impact resistance test. A pressure-sensitive adhesive layer having such properties can be suitably used even under low-temperature usage conditions.
[0063] Furthermore, it is preferred that the adhesive layer does not peel off when left at room temperature for one month after the drop impact resistance test. An adhesive layer having such properties tends to have excellent storage stability.
[0064] The pressure-sensitive adhesive layer has a temperature of 20°C, 1.0×10 3 Hz~10 4 The lower limit of the dielectric loss tangent at Hz is preferably 0.75 or more, more preferably 0.85 or more, further preferably 0.95 or more, and particularly preferably 1.15 or more. In addition, the upper limit is preferably 2.6 or less, more preferably 2.4 or less, further preferably 2.2 or less, and particularly preferably 2.0 or less. 3 Hz~10 4 The dielectric loss tangent in the high-speed region of Hz is 0.75 or more, which makes it easy to demonstrate drop impact resistance. 3 Hz~10 4 The dielectric loss tangent in a high-speed region such as Hz is 2.6 or less, and cohesive failure of the adhesive layer can be easily prevented.
[0065] The thickness of the adhesive layer is preferably 5 to 300 μm, more preferably 8 to 200 μm, and particularly preferably 10 to 100 μm. A thickness of 5 μm or more can easily exhibit drop impact resistance, while a thickness of 300 μm or less can provide excellent handleability and manufacturability.
[0066] The method for preparing the pressure-sensitive adhesive layer is not particularly limited, and may be, for example, preparing the pressure-sensitive adhesive composition described below, applying (coating) the composition on a substrate or a release liner, and, if necessary, irradiating the composition with active energy rays, heating and drying the composition, and the like.
[0067] It should be noted that the adhesive composition can be applied by a known coating method, for example, a coating machine such as a gravure roll coater, a reverse roll coater, a lick roll coater, a dip roll coater, a bar coater, a knife coater, a spray coater, a comma coater, or a direct coater can be used.
[0068] In addition, the adhesive composition preferably does not contain an organic solvent or substantially does not contain an organic solvent. The organic solvent is not particularly limited as long as it is an organic compound used as a solvent, and examples thereof include: hydrocarbon solvents such as cyclohexane, hexane, and heptane; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; alcohol solvents such as methanol, ethanol, butanol, and isopropanol, etc. It should be noted that the organic solvent may be a mixed solvent containing two or more organic solvents.
[0069] The above-mentioned adhesive composition "substantially does not contain" an organic solvent means that the organic solvent is not actively mixed except when the organic solvent is inevitably mixed in. Specifically, the adhesive composition can be said to be substantially free of an organic solvent when the content of the organic solvent in the adhesive composition is 1.0 mass % or less (preferably 0.5 mass % or less, more preferably 0.2 mass % or less) relative to the total amount (100 mass %) of the adhesive composition.
[0070] The adhesive composition for forming the adhesive layer is preferably an adhesive composition containing an acrylic polymer as a base polymer. In addition, the adhesive composition may also contain a hydrogenated polyolefin resin, a multifunctional (meth)acrylate, a silane coupling agent, and other additives described below. It should be noted that the acrylic polymer may be used alone or in combination of two or more.
[0071] The content of the acrylic polymer is not particularly limited, but is preferably 30 to 90% by mass, and more preferably 40 to 80% by mass, based on the total amount (100% by mass) of the pressure-sensitive adhesive composition.
[0072] There are no particular restrictions on the adhesive composition for forming an adhesive layer containing an acrylic polymer as a main component, and examples thereof include: a composition containing an acrylic polymer as an essential component; a composition containing a mixture of monomer components constituting an acrylic polymer (sometimes referred to as a "monomer mixture") or a partial polymer thereof as an essential component, etc. As the former, for example, a so-called water-dispersible composition (emulsion composition) can be cited, and as the latter, for example, a so-called active energy ray-curable composition can be cited. Among them, the adhesive composition is preferably a composition containing the above-mentioned monomer mixture or a partial polymer thereof as an essential component.
[0073] In this specification, the above-mentioned "mixture of monomer components" includes the case where it is composed of a single monomer component and the case where it is composed of two or more monomer components. In addition, the above-mentioned "partial polymer of a mixture of monomer components" refers to a composition in which one or more monomer components among the constituent monomer components of the above-mentioned "mixture of monomer components" are partially polymerized.
[0074] An acrylic polymer is a polymer (polymer) containing an acrylic monomer (acrylic monomer) as an essential monomer unit (monomer unit, monomer constituent unit). In other words, an acrylic polymer is a polymer containing a structural unit derived from an acrylic monomer as a structural unit. That is, an acrylic polymer is a polymer composed (formed) of an acrylic monomer as an essential monomer component. It should be noted that in this specification, "(meth)acrylic acid" means either or both of "acrylic acid" and "methacrylic acid", and the same applies to others. The weight average molecular weight of the acrylic polymer is not particularly limited, and is preferably 100,000 to 5,000,000.
[0075] The acrylic polymer in the pressure-sensitive adhesive composition is preferably a polymer containing, as a monomer unit, an alkyl (meth)acrylate having a linear or branched alkyl group (hereinafter sometimes simply referred to as “alkyl (meth)acrylate”).
[0076] Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate (n-butyl (meth)acrylate), isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and tert-butyl (meth)acrylate. Alkyl (meth)acrylates having an alkyl group with 1 to 24 carbon atoms, such as nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, etc. It should be noted that the alkyl (meth)acrylates may be used alone or in combination of two or more.
[0077] As the alkyl (meth)acrylate, alkyl acrylate is preferred over alkyl methacrylate in that the polymerization time of the acrylic polymer can be shortened to improve productivity. In particular, when the acrylic polymer is cured by radiation polymerization, alkyl acrylate is preferred.
[0078] Among them, from the viewpoint of exerting a low dielectric constant and drop impact resistance, the above-mentioned alkyl (meth)acrylate is preferably an alkyl (meth)acrylate having an alkyl group with 1 to 18 carbon atoms, more preferably methyl methacrylate (MMA), butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), isostearyl acrylate (ISTA), and particularly preferably 2-ethylhexyl acrylate (2EHA).
[0079] The content (ratio) of the alkyl (meth)acrylate in all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer) is not particularly limited. From the viewpoint of exerting a low dielectric constant and drop impact resistance, the content (ratio) of the alkyl (meth)acrylate is preferably 30% to 95% by mass, more preferably 35% to 90% by mass, and even more preferably 40% to 85% by mass, relative to the total amount (100% by mass) of the monomer components constituting the acrylic polymer.
[0080] It should be noted that in this specification, the “total amount of monomer components constituting the acrylic polymer” also includes monomer components separately added to the adhesive composition containing the acrylic polymer in the above-mentioned adhesive composition for the purpose of adjusting the dielectric constant of the adhesive layer, etc.
[0081] In the above-mentioned adhesive composition, the acrylic polymer may contain, in addition to the above-mentioned (meth) alkyl acrylate, a copolymerizable functional group-containing monomer (copolymerizable functional group-containing monomer) as a monomer unit. That is, the acrylic polymer may contain a functional group-containing monomer as a constituent monomer component. It should be noted that the functional group-containing monomer may be used alone or in combination of two or more.
[0082] As the above-mentioned functional group-containing monomer, preferably a hydroxyl-containing monomer can be cited. When the acrylic polymer contains a hydroxyl-containing monomer as a monomer unit, it is easy to polymerize when the constituent monomer components are polymerized, and in addition, cohesive force can be improved. In addition, the interaction with the adherend interface can be improved. Therefore, strong adhesion is easily obtained.
[0083] The above-mentioned hydroxyl-containing monomer refers to a monomer having at least one hydroxyl group in the molecule. In addition, a monomer having at least one hydroxyl group in the molecule and at least one carboxyl group in the molecule is a carboxyl-containing monomer, not a hydroxyl-containing monomer. As the above-mentioned hydroxyl-containing monomer, there is no particular limitation, and specifically, for example, hydroxyl-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, (meth)acrylate (4-hydroxymethylcyclohexyl)methyl, vinyl alcohol, allyl alcohol, etc. can be cited. Among them, as the above-mentioned hydroxyl-containing monomer, from the viewpoint of easily obtaining good cohesive force and easily obtaining adhesive reliability at high temperature, hydroxyl-containing (meth) acrylate is preferred, and 2-hydroxyethyl acrylate (HEA), 2-hydroxypropyl acrylate (HPA), and 4-hydroxybutyl acrylate (4HBA) are more preferred. It should be noted that the hydroxyl-containing monomer can be used alone or in combination of two or more.
[0084] In addition, as the functional group-containing monomer, a nitrogen atom-containing monomer is preferably mentioned. When the acrylic polymer contains a nitrogen atom-containing monomer as a monomer unit, it is easy to obtain moderate cohesive force, thereby easily obtaining strong adhesiveness and easily obtaining excellent anti-foaming and peeling properties.
[0085] A nitrogen atom-containing monomer refers to a monomer having at least one nitrogen atom in the molecule (in one molecule). However, the above-mentioned hydroxyl-containing monomer does not include the above-mentioned nitrogen atom-containing monomer. That is, in this specification, a monomer having a hydroxyl group and a nitrogen atom in the molecule is included in the nitrogen atom-containing monomer. In addition, a monomer having at least one nitrogen atom in the molecule and at least one carboxyl group in the molecule is a carboxyl-containing monomer, not a nitrogen atom-containing monomer.
[0086] As the nitrogen atom-containing monomer, from the viewpoint of exerting strong adhesive force, N-vinyl cyclic amide, (meth)acrylamide, etc. are preferred. In addition, the nitrogen atom-containing monomer can be used alone or in combination of two or more.
[0087] As the N-vinyl cyclic amide, an N-vinyl cyclic amide represented by the following formula (1) is preferred from the viewpoint of easily obtaining good cohesive force and easily obtaining high-temperature adhesive reliability.
[0088]
[0089] (In formula (1), R 1 represents a divalent organic group. )
[0090] In the above formula (1), R1 It is a divalent organic group, preferably a divalent saturated hydrocarbon group or a divalent unsaturated hydrocarbon group, and more preferably a divalent saturated hydrocarbon group (for example, an alkylene group having 3 to 5 carbon atoms).
[0091] As the N-vinyl cyclic amide represented by the above formula (1), from the viewpoint of further exerting strong adhesiveness, N-vinyl-2-pyrrolidone (NVP), N-vinyl-2-piperidone, N-vinyl-2-caprolactam, N-vinyl-3-morpholinone, N-vinyl-1,3- More preferred are oxazine-2-one, N-vinyl-3,5-morpholinedione, etc., more preferred are N-vinyl-2-pyrrolidone and N-vinyl-2-caprolactam, and further preferred is N-vinyl-2-pyrrolidone.
[0092] Examples of the (meth)acrylamides include (meth)acrylamide, N-alkyl (meth)acrylamide, and N,N-dialkyl (meth)acrylamide. Examples of the N-alkyl (meth)acrylamide include N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-n-butyl (meth)acrylamide, and N-octylacrylamide. In addition, the N-alkyl (meth)acrylamide also includes (meth)acrylamide having an amino group, such as dimethylaminoethyl (meth)acrylamide, diethylaminoethyl (meth)acrylamide, and dimethylaminopropyl (meth)acrylamide. Examples of the N,N-dialkyl (meth)acrylamide include N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-diisopropyl (meth)acrylamide, N,N-di(n-butyl) (meth)acrylamide, and N,N-di(tert-butyl) (meth)acrylamide.
[0093] In addition, the (meth)acrylamides include, for example, various N-hydroxyalkyl (meth)acrylamides. Examples of the N-hydroxyalkyl (meth)acrylamides include N-methylol (meth)acrylamide, N-(2-hydroxyethyl) (meth)acrylamide, N-(2-hydroxypropyl) (meth)acrylamide, N-(1-hydroxypropyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(2-hydroxybutyl) (meth)acrylamide, N-(3-hydroxybutyl) (meth)acrylamide, N-(4-hydroxybutyl) (meth)acrylamide, and N-methyl-N-(2-hydroxyethyl) (meth)acrylamide.
[0094] The (meth)acrylamides include, for example, various N-alkoxyalkyl (meth)acrylamides, such as N-methoxymethyl (meth)acrylamide and N-butoxymethyl (meth)acrylamide.
[0095] In addition, examples of nitrogen atom-containing monomers other than the above-mentioned N-vinyl cyclic amides and the above-mentioned (meth)acrylamides include amino group-containing monomers such as (meth)aminoethyl acrylate, dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; (meth)acryloylmorpholine, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazole, N-vinylpyrazine, N-vinylmorpholine, N-vinylpyrazole, vinylpyridine, vinylpyrimidine, vinyl Azoles, vinyl isocyanates Heterocyclic monomers such as oxazole, vinylthiazole, vinylisothiazole, vinylpyridazine, (meth)acryloylpyrrolidone, (meth)acryloylpyrrolidine, (meth)acryloylpiperidine, N-methylvinylpyrrolidone, etc.; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide, etc.; N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide Itaconimide monomers such as itaconimide, N-(2-ethylhexyl) itaconimide, N-lauryl itaconimide, and N-cyclohexyl itaconimide; succinimide monomers such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyoctamethylenesuccinimide; and isocyanate monomers such as 2-(meth)acryloyloxyethyl isocyanate.
[0096] Examples of copolymerizable monomers in the acrylic polymer include, in addition to the above-mentioned nitrogen atom-containing monomers and hydroxyl-containing monomers: monomers containing an alicyclic structure [e.g., cyclopropyl (meth)acrylate, cyclobutyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, cyclooctyl (meth)acrylate, isobornyl (meth)acrylate, tetrahydrodicyclopentadienyl (meth)acrylate]; alkoxyalkyl (meth)acrylates [e.g., 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, propyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, 4-ethoxybutyl (meth)acrylate, etc.]; epoxy group-containing monomers [for example, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, etc.]; sulfonic acid group-containing monomers [for example, sodium vinyl sulfonate, etc.]; phosphoric acid group-containing monomers; (meth)acrylates having an aromatic hydrocarbon group [for example, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, etc.]; vinyl esters [for example, vinyl acetate, vinyl propionate, etc.]; aromatic vinyl compounds [for example, styrene, vinyl toluene, etc.]; olefins or dienes [for example, ethylene, propylene, butadiene, isoprene, isobutylene, etc.]; vinyl ethers [for example, vinyl alkyl ether, etc.]; vinyl chloride, etc.
[0097] The above-mentioned adhesive composition preferably does not contain or substantially does not contain a carboxyl group-containing monomer as a monomer component constituting an acrylic polymer. By not containing or substantially not containing a carboxyl group-containing monomer, in a touch panel bonded with an optical component (touch sensor film) having metal wiring such as a metal mesh film and a silver nanowire film, an anti-corrosion effect on the metal wiring can be obtained. The content of the carboxyl group-containing monomer is preferably 1 ng / cm relative to the total amount of the above-mentioned adhesive composition. 2 Below (e.g. 0-1 ng / cm 2 ), more preferably 0.8 ng / cm 2 Below (e.g. 0 to 0.8 ng / cm 2 ), more preferably 0.5 ng / cm 2 Below (e.g. 0 to 0.5 ng / cm 2 ) can be said to be substantially free of. It should be noted that, as the above-mentioned carboxyl group-containing monomer, for example, (meth) acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, etc. can be cited. In addition, the above-mentioned carboxyl group-containing monomer also includes anhydride group-containing monomers such as maleic anhydride and itaconic anhydride.
[0098] The content (ratio) of the functional group-containing monomer relative to the total amount of monomer components constituting the acrylic polymer (100% by mass) is not particularly limited, but is preferably 5% to 40% by mass, more preferably 7% to 35% by mass, and further preferably 10% to 30% by mass from the viewpoint of exerting appropriate adhesiveness.
[0099] In the case where the above-mentioned acrylic polymer contains a hydroxyl-containing monomer and a nitrogen atom-containing monomer as the functional group-containing monomer components constituting the polymer, the content ratio of the functional group-containing monomer having a larger content among the hydroxyl-containing monomer and the nitrogen atom-containing monomer is preferably 60% by mass or more, more preferably 65% by mass or more, and further preferably 70% by mass or more, relative to the total amount (100% by mass) of the hydroxyl-containing monomer and the nitrogen atom-containing monomer.
[0100] In the polymerization of the acrylic polymer, a polymerization initiator such as a thermal polymerization initiator or a photopolymerization initiator (photoinitiator) may be used depending on the type of polymerization reaction. The polymerization initiator may be used alone or in combination of two or more.
[0101] As the above-mentioned photopolymerization initiator, there is no particular limitation, and examples thereof include: benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-ketol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, thioxanthone photopolymerization initiators, etc. It should be noted that the photopolymerization initiator can be used alone or in combination of two or more.
[0102] Examples of the benzoin ether photopolymerization initiator include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of the acetophenone photopolymerization initiator include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexylphenyl ketone, 4-phenoxydichloroacetophenone, and 4-(tert-butyl)dichloroacetophenone. Examples of the α-ketol photopolymerization initiator include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of the aromatic sulfonyl chloride photopolymerization initiator include 2-naphthalenesulfonyl chloride. Examples of the photoactive oxime-based photopolymerization initiator include 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)-oxime. Examples of the benzoin-based photopolymerization initiator include benzoin. Examples of the benzyl-based photopolymerization initiator include benzyl. Examples of the benzophenone-based photopolymerization initiator include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenylketone, and the like. Examples of the ketal-based photopolymerization initiator include benzyldimethylketal, and the like. Examples of the thioxanthone-based photopolymerization initiator include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.
[0103] The amount of the photopolymerization initiator used is not particularly limited, and is, for example, preferably 0.001 to 1 part by mass, more preferably 0.01 to 0.50 parts by mass, based on 100 parts by mass of all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer).
[0104] In addition, the above-mentioned thermal polymerization initiator is not particularly limited, and examples thereof include: azo polymerization initiators, peroxide polymerization initiators (such as dibenzoyl peroxide, tert-butyl permaleate, etc.), redox polymerization initiators, etc. Among them, the azo polymerization initiators disclosed in Japanese Patent Publication No. 2002-69411 are preferred. Examples of the above-mentioned azo polymerization initiators include: 2,2'-azobisisobutyronitrile (hereinafter sometimes referred to as "AIBN"), 2,2'-azobis-2-methylbutyronitrile (hereinafter sometimes referred to as "AMBN"), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis-4-cyanovaleric acid, etc.
[0105] The amount of the thermal polymerization initiator used is not particularly limited. For example, in the case of the azo polymerization initiator, the amount is preferably 0.05 to 0.5 parts by mass, more preferably 0.1 to 0.3 parts by mass, relative to 100 parts by mass of all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer).
[0106] The adhesive composition has the acrylic polymer as a main component, and further from the viewpoint of lowering the dielectric constant and falling impact resistance, preferably a monomer component different from the acrylic polymer (hereinafter sometimes referred to as "another added monomer") is added. It should be noted that the above-mentioned other added monomers can be used alone or in combination of two or more.
[0107] As the above-mentioned additionally added monomer, from the viewpoint of realizing low dielectric constant and drop impact resistance, it is preferred to be a compound proposed as the above-mentioned (meth) alkyl acrylate and / or the above-mentioned functional group-containing monomer, and more preferably a compound proposed as the above-mentioned (meth) alkyl acrylate and / or the above-mentioned hydroxyl-containing monomer. Specifically, as (meth) alkyl acrylate, methyl methacrylate (MMA), butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), isostearyl acrylate (ISTA), etc. can be cited. In addition, as a hydroxyl-containing monomer, hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 2-hydroxybutyl (meth) acrylate, 3-hydroxypropyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate, 6-hydroxyhexyl (meth) acrylate, hydroxyoctyl (meth) acrylate, hydroxydecyl (meth) acrylate, hydroxylauryl (meth) acrylate, hydroxyl (meth) acrylate (4-hydroxymethylcyclohexyl) methyl ester and the like (meth) acrylate; vinyl alcohol, allyl alcohol, etc.
[0108] The amount of the monomer added is not particularly limited. From the viewpoint of exerting low dielectric constant and drop impact resistance, the lower limit is preferably 25% by mass or more, more preferably 30% by mass or more, further preferably 35% by mass or more, and particularly preferably 40% by mass or more, relative to 100% by mass of all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer). In addition, the upper limit is preferably 75% by mass or less, more preferably 70% by mass or less, further preferably 65% by mass or less, and particularly preferably 60% by mass or less.
[0109] In addition, the above-mentioned adhesive composition is preferably an adhesive composition with an acrylic polymer as the main component and a hydrogenated polyolefin resin. Hydrogenated polyolefin resin is a material with a low dielectric constant. By being matched to the above-mentioned acrylic polymer, the dielectric constant can be reduced, so that in a touch panel with an optical component (touch sensor film) having metal wiring such as a metal mesh film and a silver nanowire film, the erroneous operation of the touch operation can be suppressed. In addition, it is possible to realize an adhesive layer with high flexibility without the need for low molecular weight of an acrylic polymer, and even in the case of an optical component (touch sensor film) having metal wiring such as a metal mesh film and a silver nanowire film, it is possible to fully relax the stress with the metal wiring, thereby preventing uneven display, which is preferred from this aspect. In addition, the compatibility of hydrogenated polyolefin resin and acrylic polymer is also excellent, so it is preferred from the aspect of being able to maintain the transparency of the above-mentioned adhesive layer at a higher level. Hydrogenated polyolefin resins can be used alone or in combination of two or more.
[0110] The hydrogenated polyolefin resin is preferably a hydrogenated polyolefin resin that exhibits liquid fluidity at 25° C., from the perspective of being able to realize a highly flexible adhesive layer and being able to sufficiently relax the stress on the metal wiring even when an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded, thereby preventing display unevenness. The hydrogenated polyolefin resin exhibiting liquid fluidity at 25° C. means that the viscosity measured at 25° C. using a B-type viscometer is 10,000 mPa·s or less.
[0111] The hydrogenated polyolefin resin is obtained by reducing the carbon-carbon double bonds contained in the polyolefin resin by a hydrogenation reaction. Since the carbon-carbon double bonds in the hydrogenated polyolefin resin are reduced, it is not easy to cause polymerization inhibition when the above-mentioned adhesive composition is cured by ultraviolet irradiation, and it is not easy to cause a decrease in polymerization rate and low molecular weight, so the adhesive reliability of the above-mentioned adhesive composition at high temperature can be maintained at a high level.
[0112] From the viewpoint of being less likely to cause inhibition of polymerization and adhesive reliability at high temperatures, the hydrogenation rate of the hydrogenated polyolefin resin is preferably 90% or more, more preferably 95% or more, and even more preferably 97% or more. The upper limit of the hydrogenation rate is not particularly limited, but is theoretically 100%, and in practice can be 99.9% or less, or 99.8% or less. It should be noted that the hydrogenation rate of the hydrogenated polyolefin resin can be adjusted by using 1 The H-NMR measurement can be used to determine the amount of double bonds remaining in the hydrogenated polyolefin resin.
[0113] From the viewpoint of being less likely to cause inhibition and adhesive reliability at high temperatures, the iodine value (Ig / 100g) of the hydrogenated polyolefin resin is preferably 30 or less, more preferably 25 or less, and further preferably 20 or less. The lower limit of the iodine value is not particularly limited, but may be 0.1 or more, or 0.2 or more. It should be noted that the iodine value is a value measured in accordance with JIS K 0070-1992.
[0114] The number average molecular weight (Mn) of the hydrogenated polyolefin resin is preferably 1000 to 5000 from the viewpoint of imparting appropriate stress relaxation and fluidity to the adhesive layer and improving compatibility with the acrylic polymer. The number average molecular weight (Mn) is preferably 1000 or more, more preferably 1500 or more, and further preferably 1800 or more from the viewpoint of imparting appropriate stress relaxation and fluidity to the adhesive composition. The number average molecular weight (Mn) is preferably 5000 or less, more preferably 4800 or less, and further preferably 4600 or less from the viewpoint of improving compatibility with the acrylic polymer and maintaining the transparency of the adhesive composition at a higher level.
[0115] From the perspective of imparting appropriate stress relaxation and fluidity to the adhesive layer, improving compatibility with acrylic polymers, maintaining high transparency, and suppressing haze, the polydispersity (Mw / Mn) of the hydrogenated polyolefin resin is preferably less than 2.0, and more preferably less than 1.8. The lower limit of the polydispersity is not particularly limited, but it can be 1.0 or more than 1.1 in practice. It should be noted that the number average molecular weight (Mn) and polydispersity (Mw / Mn) of the hydrogenated polyolefin resin are values determined by gel permeation chromatography (GPC) and calculated based on polystyrene.
[0116] The hydrogenated polyolefin resin includes hydrogenated polyolefin. The pressure-sensitive adhesive composition preferably includes hydrogenated polyolefin as the hydrogenated polyolefin resin, because the dielectric constant is reduced and erroneous operation of touch operation in the touch panel is suppressed.
[0117] The hydrogenated polyolefin is a hydrogenated product of a polymer (polyolefin) having a structural unit derived from an olefin. The hydrogenated polyolefin includes hydrogenated products of homopolymers and copolymers of α-olefins such as ethylene, propylene, 1-butene, isobutylene, and 1-hexene; diene compounds such as butadiene and isoprene; and aromatic vinyl compounds such as styrene. As the hydrogenated polyolefin, the hydrogenated product of the homopolymer or copolymer of the diene compound is preferred, for example, hydrogenated polybutadiene, hydrogenated polyisoprene, etc. The hydrogenated polyolefin can be used alone or in combination of two or more.
[0118] From the viewpoint of reducing the dielectric constant and suppressing erroneous operation of touch operation in the touch panel, the hydrogenated polyolefin-based resin preferably contains a hydrogenated polyolefin polyol in addition to the hydrogenated polyolefin.
[0119] The hydrogenated polyolefin polyol is a compound obtained by modifying the terminal of the hydrogenated polyolefin with a hydroxyl group. As the hydrogenated polyolefin polyol, a hydroxyl-modified product of a hydrogenated product of a homopolymer or copolymer of a diene compound is preferred, for example, hydrogenated polybutadiene polyol, hydrogenated polyisoprene polyol, etc. The hydrogenated polyolefin polyol can be used alone or in combination of two or more.
[0120] As the above-mentioned hydrogenated polyolefin and hydrogenated polyolefin polyol, hydrogenated polybutadiene and hydrogenated polybutadiene polyol are respectively preferred from the perspective of being able to realize a highly flexible adhesive layer and being able to fully relax the stress with the metal wiring even when an optical component (touch sensor film) having metal wiring such as a metal mesh film and a silver nanowire film is bonded, thereby preventing display unevenness.
[0121] As the hydrogenated polybutadiene, a hydrogenated polybutadiene represented by the following formula (2) is preferred, and as the hydrogenated polybutadiene polyol, a hydrogenated polybutadiene polyol represented by the following formula (3) is preferred.
[0122]
[0123] In the above formula, m represents the degree of polymerization of the hydrogenated polybutadiene.
[0124] As hydrogenated polyolefins and hydrogenated polyolefin polyols, commercial products can be used. Commercial products of hydrogenated polyolefins include: trade names "BI-2000", "BI-3000" (all manufactured by Nippon Soda Co., Ltd.), etc. Commercial products of hydrogenated polyolefin polyols include: trade names "GI-1000", "GI-2000", "GI-3000" (all manufactured by Nippon Soda Co., Ltd.), trade name "EPOL" (manufactured by Idemitsu Kosan Co., Ltd.), etc.
[0125] The content of the hydrogenated polyolefin resin is not particularly limited. From the viewpoint of reducing the dielectric constant and thus suppressing the erroneous operation of the touch operation in the touch panel, the content of the hydrogenated polyolefin resin may be preferably 1 part by mass or more, more preferably 2 parts by mass or more, and further preferably 3 parts by mass or more relative to 100 parts by mass of the acrylic polymer. On the other hand, from the viewpoint of suppressing the increase of haze, ensuring higher transparency, and being able to highly maintain the adhesive force and adhesive reliability at high temperatures, the content of the hydrogenated polyolefin resin is preferably 40 parts by mass or less, more preferably 35 parts by mass or less, and further preferably 30 parts by mass or less.
[0126] The content of the hydrogenated polyolefin polyol is not particularly limited. From the viewpoint of reducing the dielectric constant and thus suppressing the erroneous operation of the touch operation in the touch panel, the content of the hydrogenated polyolefin polyol may be preferably 1 part by mass or more, more preferably 3 parts by mass or more, and further preferably 5 parts by mass or more relative to 100 parts by mass of the acrylic polymer. On the other hand, from the viewpoint of suppressing the increase of haze, ensuring higher transparency, and being able to highly maintain the adhesive force and adhesive reliability at high temperatures, the content of the hydrogenated polyolefin polyol is preferably 40 parts by mass or less, more preferably 35 parts by mass or less, further preferably 30 parts by mass or less, and particularly preferably 25 parts by mass or less.
[0127] The weight ratio of the content of hydrogenated polyolefin to the content of hydrogenated polyolefin polyol in the above-mentioned adhesive composition (hydrogenated polyolefin / hydrogenated polyolefin polyol) is not particularly limited. From the perspective of reducing the dielectric constant and thus suppressing the erroneous operation of the touch operation in the touch panel, it is preferably 1 / 99 or more, more preferably 2 / 98 or more, and can be 3 / 97 or more or 4 / 96 or more. In addition, from the perspective of suppressing the increase of haze and ensuring higher transparency, the above ratio is preferably 90 / 10 or less, more preferably 80 / 20 or less, further preferably 70 / 30 or less, and can be 55 / 45 or less, 45 / 55 or less, or 30 / 70 or less.
[0128] The pressure-sensitive adhesive composition preferably further contains a polyfunctional (meth)acrylate. The polyfunctional (meth)acrylate functions as a crosslinking component, and the pressure-sensitive adhesive composition tends to have appropriate cohesive strength.
[0129] Examples of the multifunctional (meth)acrylate include hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, and urethane acrylate. It should be noted that the multifunctional (meth)acrylate may be used alone or in combination of two or more.
[0130] The content (ratio) of the multifunctional (meth) acrylate is not particularly limited. From the viewpoint that the adhesive layer has a moderate cohesive force, the content (ratio) of the multifunctional (meth) acrylate is preferably 0.001 parts by mass or more, more preferably 0.002 parts by mass or more, further preferably 0.005 parts by mass or more, and can be 0.01 parts by mass or more, relative to 100 parts by mass of the acrylic polymer. In addition, from the perspective of being able to achieve a highly flexible adhesive layer, being able to fully relax the stress with the metal wiring, and thus preventing uneven display, the content (ratio) of the multifunctional (meth) acrylate is preferably 0.5 parts by mass or less, more preferably 0.35 parts by mass or less, further preferably 0.2 parts by mass or less, and can be 0.1 parts by mass or less.
[0131] The adhesive composition preferably further contains an ultraviolet absorber. The ultraviolet absorber is not particularly limited, and examples thereof include triazine ultraviolet absorbers, benzotriazole ultraviolet absorbers, benzophenone ultraviolet absorbers, hydroxybenzophenone ultraviolet absorbers, salicylate ultraviolet absorbers, and cyanoacrylate ultraviolet absorbers, and these ultraviolet absorbers can be used alone or in combination of two or more.
[0132] As the triazine-based ultraviolet absorber, specifically, 2,4-bis[{4-(4-ethylhexyloxy)-4-hydroxy}-phenyl]-6-(4-methoxyphenyl)-1,3,5-triazine (Tinosorb S, manufactured by BASF), 2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (TINUVIN 460, manufactured by BASF), a reaction product of 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-hydroxyphenyl and [(C10-C16 (mainly C12-C13) alkoxy)methyl]ethylene oxide (TINUVIN 400, manufactured by BASF), 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl]-5-[3-(dodecyloxy)-2-hydroxypropoxy]phenol), reaction product of 2-(2,4-dihydroxyphenyl)-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and glycidyl acid (2-ethylhexyl) ester (TINUVIN 405, manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]-phenol (TINUVIN 1577, manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]-phenol (ADK STAB LA46, manufactured by ADEKA), 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenyl)-1,3,5-triazine (TINUVIN 479, manufactured by BASF), and the like.
[0133] As the benzotriazole ultraviolet absorber, 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN 928, manufactured by BASF), 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole (TINUVIN PS, manufactured by BASF), an ester compound of phenylpropionic acid and 3-(2H-benzotriazole-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy (C7-C9 side chain and linear alkyl) (TINUVIN 384-2, manufactured by BASF), 2-(2H-benzotriazole-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN 928, manufactured by BASF), 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole (TINUVIN PS, manufactured by BASF), an ester compound of phenylpropionic acid and 3-(2H-benzotriazole-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy (C7-C9 side chain and linear alkyl) (TINUVIN 384-2, manufactured by BASF), 900, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN 928, manufactured by BASF), 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionic acid methyl ester / polyethylene glycol 300 reaction product (TINUVIN 1130, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-p-cresol (TINUVIN P, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN 234, manufactured by BASF), 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol (TINUVIN 326, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-di-tert-amylphenol (TINUVIN 328, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN 329, manufactured by BASF), reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate and polyethylene glycol 300 (TINUVIN 213, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-dodecyl--4-methylphenol (TINUVIN 571, manufactured by BASF), 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidomethyl)-5-methylphenyl]benzotriazole (Sumisorb 250, manufactured by Sumitomo Chemical Co., Ltd.), and the like.
[0134] Examples of the benzophenone-based ultraviolet absorbers (benzophenone-based compounds) and hydroxybenzophenone-based ultraviolet absorbers (hydroxybenzophenone-based compounds) include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid (anhydrous salt and trihydrate salt), 2-hydroxy-4-octyloxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 4-benzyloxy-2-hydroxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, and 2,2'-dihydroxy-4,4-dimethoxybenzophenone.
[0135] Examples of the salicylate ultraviolet absorber (salicylate compound) include phenyl 2-acryloxybenzoate, phenyl 2-acryloxy-3-methylbenzoate, phenyl 2-acryloxy-4-methylbenzoate, phenyl 2-acryloxy-5-methylbenzoate, phenyl 2-acryloxy-3-methoxybenzoate, phenyl 2-hydroxybenzoate, phenyl 2-hydroxy-3-methylbenzoate, phenyl 2-hydroxy-4-methylbenzoate, phenyl 2-hydroxy-5-methylbenzoate, phenyl 2-hydroxy-3-methoxybenzoate, phenyl 3,5-di-tert-butyl-4-hydroxybenzoate (TINUVIN 120, manufactured by BASF), and the like.
[0136] Examples of the cyanoacrylate ultraviolet absorber (cyanoacrylate compound) include 2-cyanoacrylate alkyl esters, 2-cyanoacrylate cycloalkyl esters, 2-cyanoacrylate alkoxyalkyl esters, 2-cyanoacrylate alkenyl esters, and 2-cyanoacrylate alkynyl esters.
[0137] The content (ratio) of the ultraviolet absorber is not particularly limited. From the viewpoint that the adhesive layer has a moderate cohesive force, the content (ratio) of the ultraviolet absorber is preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, further preferably 0.05 parts by mass or more, and may be 0.1 parts by mass or more, relative to 100 parts by mass of the acrylic polymer. In addition, the content (ratio) of the ultraviolet absorber is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, further preferably 5 parts by mass or less, and may be 3 parts by mass or less, relative to 100 parts by mass of the acrylic polymer.
[0138] In addition, the adhesive composition may further contain a photopolymerization initiator in addition to the photopolymerization initiator contained in the acrylic polymer. As the photopolymerization initiator in addition to the photopolymerization initiator contained in the acrylic polymer, the photopolymerization initiator exemplified as the photopolymerization initiator used in the acrylic polymer can be used. It should be noted that the photopolymerization initiator in addition to the photopolymerization initiator contained in the acrylic polymer can be used alone or in combination of two or more.
[0139] The content (ratio) of the photopolymerization initiator other than the photopolymerization initiator contained in the acrylic polymer is not particularly limited, and the content (ratio) of the photopolymerization initiator is preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, further preferably 0.05 parts by mass or more, and may be 0.1 parts by mass or more, relative to 100 parts by mass of the acrylic polymer. In addition, the content (ratio) of the photopolymerization initiator is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, further preferably 1 part by mass or less, and may be 0.5 parts by mass or less, relative to 100 parts by mass of the acrylic polymer.
[0140] The adhesive composition may contain known additives such as a crosslinking agent, a crosslinking accelerator, a tackifying resin (rosin derivatives, polyterpene resins, oil-soluble phenol resins, etc.), an anti-aging agent, a filler, a colorant (pigment, dye, etc.), a chain transfer agent, a plasticizer, a softener, a surfactant, an antistatic agent, a rust inhibitor, an antioxidant, etc., as required within a range that does not impair the characteristics of the present invention. It should be noted that such additives may be used alone or in combination of two or more.
[0141] The glass transition temperature (Tg) calculated from the acrylic polymer and the additionally added monomer in the adhesive composition is preferably above -5°C, more preferably above -4°C, and particularly preferably above -3°C. When the glass transition temperature (Tg) is above -5°C, it is easy to make the adhesive layer have a low dielectric constant, thereby exerting reworkability in a high-speed (low-temperature) region. In addition, there is no particular restriction on the upper limit, but from the perspective of exerting the minimum adhesive force, it is preferably below 20°C, more preferably below 15°C, and further preferably below 10°C.
[0142] It should be noted that the glass transition temperature (Tg) is a calculated glass transition temperature calculated by the following Fox equation. The calculated glass transition temperature is calculated based on the type and amount of each monomer component constituting the above-mentioned adhesive composition, and therefore, can be adjusted by selecting the type and amount of each monomer component.
[0143] The calculated glass transition temperature (calculated Tg) can be calculated by the following Fox formula [1].
[0144] 1 / Calculate Tg = W 1 / Tg(1) + W 2 / Tg(2) + ... + Wn / Tg(n) [1]
[0145] Here, W1, W2, ... Wn refer to the weight fractions (weight %) of monomer component (1), monomer component (2), ... monomer component (n) constituting the adhesive composition relative to all monomer components, and Tg(1), Tg(2), ... Tg(n) represent the glass transition temperatures (in absolute temperature: K) of the homopolymers of monomer component (1), monomer component (2), ... monomer component (n).
[0146] It should be noted that the "glass transition temperature (Tg) of the homopolymer" (sometimes referred to as "Tg of the homopolymer") in this specification refers to the "glass transition temperature (Tg) of the homopolymer of the monomer", specifically, the numerical values are listed in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc, 1987). It should be noted that, with respect to the Tg of the homopolymer of the monomer not described in the above-mentioned documents, except for the monomer having a polyorganosiloxane skeleton, for example, it refers to the value obtained by the following measurement method (refer to Japanese Patent Gazette No. 2007-51271). That is, 100 parts by mass of the monomer, 0.2 parts by mass of 2,2'-azobisisobutyronitrile and 200 parts by mass of ethyl acetate as a polymerization solvent are added to a reactor equipped with a thermometer, a stirrer, a nitrogen inlet pipe and a reflux condenser, and stirred for 1 hour while introducing nitrogen. In this way, the oxygen in the polymerization system is removed, and then the temperature is raised to 63°C and reacted for 10 hours. Then, it was cooled to room temperature to obtain a homopolymer solution having a solid content concentration of 33% by mass. Next, the homopolymer solution was cast on a release liner and dried to prepare a test sample (sheet-shaped homopolymer) having a thickness of about 2 mm. The test sample was then punched into a disc with a diameter of 7.9 mm, sandwiched between parallel plates, and a viscoelasticity tester (trade name "ARES", manufactured by Rheometrics) was used to apply a shear strain at a frequency of 1 Hz, and the viscoelasticity was measured by shear mode at a temperature range of -70°C to 150°C and a heating rate of 5°C / min, and the peak temperature of tanδ was used as the Tg of the homopolymer.
[0147] The pressure-sensitive adhesive composition can be prepared by mixing the acrylic polymer, a monomer component as required, a hydrogenated polyolefin resin, a polyfunctional (meth)acrylate, a silane coupling agent, and other additives, and uniformly stirring the mixture.
[0148] The adhesive sheet of the present invention may be a so-called "substrate-free" adhesive sheet (hereinafter sometimes referred to as a "substrate-free adhesive sheet") that does not have a substrate (substrate layer), or may be an adhesive sheet having a substrate (hereinafter sometimes referred to as a "substrate-free adhesive sheet"). As the above-mentioned substrate-free adhesive sheet, for example, there can be cited: a double-sided adhesive sheet consisting only of the above-mentioned adhesive layer, a double-sided adhesive sheet consisting of the above-mentioned adhesive layer and an adhesive layer other than the above-mentioned adhesive layer (sometimes referred to as "other adhesive layers"), etc. On the other hand, as an adhesive sheet with a substrate, there can be cited: an adhesive sheet having the above-mentioned adhesive layer on at least one side of the substrate, etc. Among them, a substrate-free adhesive sheet (substrate-free double-sided adhesive sheet) is preferred, and a substrate-free double-sided adhesive sheet consisting only of the above-mentioned adhesive layer is more preferred. It should be noted that the above-mentioned "substrate (substrate layer)" does not include a release liner that is peeled off when the adhesive sheet is used (pasted).
[0149] Figure 1 Schematic diagram (cross-sectional view) showing a specific example of a preferred embodiment of the adhesive sheet of the present invention, 1 represents an adhesive sheet, 10 represents an adhesive layer, and 11 and 12 represent release liners. Figure 1 In the figure, the pressure-sensitive adhesive sheet 1 is a double-sided pressure-sensitive adhesive sheet without a substrate, and both pressure-sensitive adhesive surfaces of the pressure-sensitive adhesive layer 10 are protected by release liners 11 and 12 .
[0150] The thickness (total thickness) of the adhesive sheet is not particularly limited, preferably 5 μm to 600 μm, more preferably 10 μm to 500 μm. When the thickness is above a certain value, it is preferred in terms of resistance to drop impact. In addition, when the thickness is below a certain value, it is preferred from the perspective of being easy to maintain excellent appearance during manufacture and roll storage, and being difficult to produce adhesive contamination during cutting. It should be noted that the thickness of the adhesive sheet does not include the thickness of the release liner.
[0151] The above-mentioned adhesive sheet is not particularly limited, and is preferably manufactured according to a known or customary manufacturing method. For example, when the above-mentioned adhesive sheet is a substrate-free adhesive sheet, the above-mentioned adhesive layer is formed on a release liner by the above-mentioned method and obtained. In addition, when the above-mentioned adhesive sheet is an adhesive sheet with a substrate, the above-mentioned adhesive layer can be obtained by directly forming the above-mentioned adhesive layer on the surface of the substrate (direct method), or the above-mentioned adhesive layer can be temporarily formed on the release liner, and then transferred (laminated) to the substrate, so as to obtain the above-mentioned adhesive layer on the substrate (transfer method).
[0152] In addition to the adhesive layer, the adhesive sheet may also have other layers. Examples of other layers include other adhesive layers (adhesive layers other than the adhesive layer), an intermediate layer, a primer layer, etc. It should be noted that the adhesive sheet may have two or more other layers.
[0153] As the substrate in the case where the above-mentioned adhesive sheet is an adhesive sheet with a substrate, there is no particular limitation, and for example, various optical films such as plastic films, anti-reflection (AR) films, polarizing plates, and phase difference plates can be cited. As the material of the above-mentioned plastic film, for example, polyester resins such as polyethylene terephthalate (PET), acrylic resins such as polymethyl methacrylate (PMMA), polycarbonate, triacetyl cellulose (TAC), polysulfone, polyarylate, polyimide, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, ethylene-propylene copolymer, plastic materials such as cyclic olefin polymers such as "ARTON (cyclic olefin polymer, manufactured by JSR)", "ZEONOR (cyclic olefin polymer, manufactured by Japan Zeon Co., Ltd.)" can be cited. It should be noted that these plastic materials can be used alone or in combination of two or more. In addition, the above-mentioned "substrate" refers to the part that is attached to the adherend together with the adhesive layer when the adhesive sheet is attached to the adherend. The release liner that is peeled off when the pressure-sensitive adhesive sheet is used (when attached) is not included in the “substrate”.
[0154] The thickness of the substrate is not particularly limited, and is preferably 12 μm to 500 μm, for example. It should be noted that the substrate may have any form of a single layer or a multilayer. In addition, the surface of the substrate may be appropriately subjected to a known and commonly used surface treatment such as a physical treatment such as a corona discharge treatment or a plasma treatment, or a chemical treatment such as a primer treatment.
[0155] The above-mentioned adhesive sheet can be provided with a release liner on the adhesive face until use. It should be noted that, when the above-mentioned adhesive sheet is a double-sided adhesive sheet, each adhesive face can be protected by 2 release liners respectively, and can also be protected by the release liner of the release face wound into a roll-shaped form by 1 two sides. The release liner is used as a protective material for adhesive layer and is peeled off when being pasted on the adherend. In addition, when the above-mentioned adhesive sheet is a substrate-free adhesive sheet, the release liner also plays the effect of the support as the adhesive layer. It should be noted that it is not necessary to set a release liner.
[0156] As the above-mentioned release liner, there is no particular restriction, for example, there can be cited: a release liner having a release layer (release treatment layer) on at least one surface of the release liner substrate, a low-adhesive release liner containing a fluorine-containing polymer, a low-adhesive release liner containing a non-polar polymer, etc. As the release treatment agent constituting the above-mentioned release layer, there is no particular restriction, for example, there can be cited: a silicone release treatment agent, a fluorine-containing release treatment agent, a long-chain alkyl release treatment agent, a release treatment agent such as molybdenum sulfide. As the above-mentioned fluorine-containing polymer, there is no particular restriction, for example, there can be cited: polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, chlorofluoroethylene-vinylidene fluoride copolymer, etc. In addition, as the above-mentioned non-polar polymer, there is no particular restriction, for example, there can be cited: olefin resins such as polyethylene (PE) and polypropylene (PP), etc. Among them, it is preferred to use a release liner having a release layer on at least one surface of the release liner substrate.
[0157] The release liner substrate is not particularly limited, and plastic films and the like can be cited. Examples of such plastic films include polyester resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT); olefin resins such as polyethylene (PE), polypropylene (PP), polymethylpentene (PMP), ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer (EVA) having α-olefin as a monomer component; polyvinyl chloride (PVC); vinyl acetate resins; polycarbonate (PC); polyphenylene sulfide (PPS); amide resins such as polyamide (nylon) and wholly aromatic polyamide (aramid); polyimide resins; and plastic films composed of polyetheretherketone (PEEK). Among them, from the viewpoints of processability, availability, workability, dustproofness, cost, and the like, a plastic film formed of a polyester resin is preferred, and a PET film is more preferred.
[0158] The release liner can be manufactured by a known conventional method. In addition, the release layer and / or the back side of the release liner can be laminated with layers such as a carrier material and a conductive treatment layer by a known method, and the release liner can have other layers (e.g., an intermediate layer, a primer layer, etc.) within a range that does not impair the effects of the present invention.
[0159] The thickness of the release liner is not particularly limited, but is preferably 12 μm to 200 μm, more preferably 25 μm to 150 μm, and even more preferably 38 μm to 125 μm, from the viewpoint of cost and handleability of the pressure-sensitive adhesive sheet during lamination.
[0160] The adhesive sheet of the present invention has the above-mentioned adhesive layer (adhesive layer formed by the above-mentioned adhesive composition), and therefore has a low dielectric constant, reduced noise, sufficient adhesive force, and excellent drop impact resistance. Therefore, the above-mentioned adhesive sheet can be used in image display devices, touch panels in which touch sensors are assembled in these image display devices, and optical components such as polarizing films, phase difference films, optical compensation films, touch sensor films, and cover films are attached to the image display panels, or can be used to attach these optical components to each other.
[0161] The adhesive sheet is preferably used for the manufacture of portable electronic devices. Examples of the portable electronic devices include: mobile phones, PHS, smart phones, tablet computers (tablet computers), mobile computers (mobile PCs), portable information terminals (PDAs), electronic organizers, portable televisions, portable radios and other portable broadcast receivers, portable game consoles, portable audio players, portable DVD players, cameras such as digital cameras, and portable video cameras.
[0162] The above adhesive sheet is preferably used, for example, for pasting components and modules of portable electronic devices to each other, fixing components and modules of portable electronic devices to the housing, etc. More specifically, it can be cited as follows: lamination of protective glass, lens (especially glass lens) with touch panel, touch sensor film (especially touch sensor film with metal wiring such as metal mesh film and silver nanowire film); lamination of polarizing film with touch panel and touch sensor; lamination of display panel with touch panel and touch sensor film; fixing of protective glass and lens (especially glass lens) to the housing; fixing of display panel to the housing; fixing of input devices such as sheet keyboard and touch panel to the housing; lamination of protective panel of information display part to the housing; lamination of housings to each other; lamination of housing and decorative sheet; fixing and lamination of various components and modules constituting portable electronic devices, etc. It should be noted that in this specification, display panel refers to a structure consisting of at least lens (especially glass lens) and touch panel. In addition, the lens in this specification is a concept that includes both transparent bodies that show the refraction of light and transparent bodies that do not have the refraction of light. That is, the lens in this specification also includes a simple window panel that does not have a refractive effect.
[0163] In addition, the adhesive sheet is preferably used for optical purposes. That is, the adhesive sheet is preferably an optical adhesive sheet for optical purposes. More specifically, for example, it is preferably used for the purpose of laminating optical components (optical component lamination), the manufacture of products (optical products) using the optical components, etc.
[0164] [Optical member with pressure-sensitive adhesive layer, image display device, touch panel]
[0165] The optical component with adhesive layer of the present invention is not particularly limited in other aspects as long as it is an optical component with adhesive layer having the adhesive sheet attached to at least one side of the optical component. The optical component with adhesive layer is formed by attaching the adhesive sheet, so it has a low dielectric constant, reduced noise, sufficient adhesive force, and can exhibit drop impact resistance.
[0166] In addition, the optical component with an adhesive layer may be an optical component with an adhesive layer in which the adhesive sheet is attached to an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film. In this case, the adhesive sheet is preferably attached to the surface of the touch sensor film on the side having the metal wiring.
[0167] Figure 2 It is a schematic diagram (cross-sectional view) showing a specific example of a preferred embodiment of the pressure-sensitive adhesive layer-attached optical member of the present invention.
[0168] exist Figure 2 In (a), 2A represents an optical component with an adhesive layer, 20 represents the above-mentioned adhesive layer, 21 represents the optical component, and 22 represents a release liner. The adhesive layer 20 is stacked on one surface of the optical component 21, and the adhesive surface of the adhesive layer 20 on the opposite side to the optical component 21 is protected by the release liner 22.
[0169] exist Figure 2 In (b), 2B represents an optical component with an adhesive layer (a touch sensor film with an adhesive layer), 20 represents the above-mentioned adhesive layer, 23 represents the touch sensor film, 22 represents a release liner, and 24 represents a metal wiring. The adhesive layer 20 is stacked on the surface of the touch sensor film 23 on which the metal wiring 24 is formed, and the adhesive surface of the adhesive layer 20 on the opposite side to the touch sensor film 23 is protected by the release liner 22.
[0170] Since the pressure-sensitive adhesive layer 20 is composed of the pressure-sensitive adhesive layer, the pressure-sensitive adhesive layer-attached optical member 2A and the pressure-sensitive adhesive layer-attached touch sensor film 2B can reduce noise generation, have sufficient adhesive strength, and exhibit drop impact resistance.
[0171] The optical member refers to a member having optical properties (for example, polarization, light refraction, light scattering, light reflection, light transmission, light absorption, light diffraction, optical rotation, and visibility). There are no particular restrictions on the substrate constituting the above-mentioned optical component, for example, the substrate constituting the image display device, touch panel and other equipment (optical equipment) or the substrate used in these equipment, such as polarizing film, wavelength plate, phase difference film, optical compensation film, brightness enhancement film, light guide plate, reflective film, anti-reflective film, hard coating film (a film hard-coated on at least one side of a plastic film such as a PET film), transparent conductive film (for example, a plastic film having an ITO layer on the surface (preferably an ITO film such as PET-ITO, polycarbonate-ITO, cycloolefin polymer-ITO), etc.), design film, decorative film, surface protection plate, prism, lens, color filter, transparent substrate (glass sensor, glass display panel (LCD, etc.), glass substrate with transparent electrode, etc.), and substrates formed by stacking them (sometimes collectively referred to as "functional films"), etc. In addition, these films may also have metal wiring such as a metal nanowire layer and a conductive polymer layer. In addition, metal fine wires may also be screen-printed on these films. It should be noted that the above-mentioned "plate" and "film" include plate-like, film-like, sheet-like and other forms, for example, "polarizing film" includes "polarizing plate" and "polarizing sheet", etc. In addition, "film" includes film sensors and the like.
[0172] In addition, the adhesive sheet can be suitably used for an optical member (touch sensor film) having a transparent conductive film (metal mesh film, silver nanowire film) in which the metal wiring is a metal mesh wiring or a silver nanowire, especially a metal mesh film. When an optical member having metal wiring such as a metal mesh film or a silver nanowire film is bonded together by the adhesive sheet, the low dielectric constant can suppress the generation of noise, and the adhesive sheet has sufficient adhesive strength and excellent drop impact resistance.
[0173] Therefore, the image display device and touch panel having the adhesive sheet can reduce erroneous operation caused by noise generation and exert drop impact resistance. Examples of the image display device include liquid crystal display devices, organic EL (electroluminescent) display devices, PDP (plasma display panel), electronic paper, etc.
[0174] Figure 3 It is a schematic diagram (cross-sectional view) showing a specific example of a preferred embodiment of the image display device of the present invention.
[0175] exist Figure 3In the figure, 3 represents an image display device, 30 and 31 represent the above-mentioned adhesive layers, 32 represents an image display panel, 33 represents a polarizing film, and 34 represents a transparent substrate. The image display device 3 is stacked with an image display panel 32, an adhesive layer 30, a polarizing film 33, an adhesive layer 31, and a transparent substrate 34 in this order.
[0176] Since the adhesive layers 30 and 31 are composed of the above-mentioned adhesive layers, the image display device 3 can suppress the generation of noise and exhibit drop impact resistance. It should be noted that one of the adhesive layers 30 and 31 may not be composed of the adhesive layer of the present invention.
[0177] The touch panel of the present invention is an image display device in which an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is incorporated.
[0178] Figure 4 It is a schematic diagram (cross-sectional view) showing a specific example of a preferred embodiment of the touch panel of the present invention.
[0179] exist Figure 4 In the figure, 4 represents a touch panel, 40 and 41 represent the above-mentioned adhesive layers, 42 represents an image display panel, 43 represents a touch sensor film, 44 represents a transparent substrate, and 45 represents a metal wiring. The touch panel 4 is stacked with an image display panel 42, an adhesive layer 40, a touch sensor film 43, an adhesive layer 41, and a transparent substrate 44 in this order.
[0180] Since the adhesive layers 40 and 41 are composed of the above-mentioned adhesive layer, the touch panel 4 can suppress the generation of noise and exhibit drop impact resistance. It should be noted that one of the adhesive layers 40 and 41 may not be composed of the above-mentioned adhesive layer.
[0181] The image display device and touch panel of the present invention may further have optical components such as a wavelength plate, a phase difference film, and an optical compensation film. These optical components may be single or multiple. There is no particular limitation on the bonding method of these optical components, and examples thereof include: (1) bonding the adhesive sheet of the present invention to the optical component with the adhesive layer of the present invention; (2) bonding the adhesive sheet other than the adhesive sheet of the present invention to the optical component with the adhesive layer of the present invention, etc.
[0182] Example
[0183] Hereinafter, the present invention will be described in more detail based on Examples, but the present invention is not limited to these Examples.
[0184] [Production Example 1: Preparation of Polymer A]
[0185] A monomer mixture consisting of 80 parts by mass of 2-ethylhexyl acrylate (2EHA), 15 parts by mass of N-vinyl-2-pyrrolidone (NVP) and 5 parts by mass of 2-hydroxyethyl acrylate (HEA) was added with 0.035 parts by mass of a photopolymerization initiator (trade name "Omnirad 184", manufactured by IGM Resins BV) and 0.035 parts by mass of a photopolymerization initiator (trade name "Omnirad 651", manufactured by IGM Resins BV), and then irradiated with ultraviolet rays until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measuring temperature 30°C) reached about 20 Pa·s, thereby obtaining a polymer A in which part of the above-mentioned monomer components was polymerized.
[0186] [Production Example 2: Preparation of Polymer B]
[0187] 0.05 parts by mass of a photopolymerization initiator (trade name "Omnirad 184", manufactured by IGM Resins BV) and 0.05 parts by mass of a photopolymerization initiator (trade name "Omnirad 651", manufactured by IGM Resins BV) were added to a monomer mixture consisting of 40 parts by mass of 2-ethylhexyl acrylate (2EHA), 40 parts by mass of isostearyl acrylate (ISTA), 19 parts by mass of N-vinyl-2-pyrrolidone (NVP) and 1 part by mass of 4-hydroxybutyl acrylate (4-HBA), and then irradiated with ultraviolet rays until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measuring temperature 30°C) reached about 20 Pa·s, thereby obtaining a polymer B in which part of the above-mentioned monomer components was polymerized.
[0188] [Example 1]
[0189] To 100 parts by mass of the polymer A obtained in Production Example 1, 80 parts by mass of isostearyl acrylate (ISTA), 20 parts by mass of 2-hydroxyethyl acrylate (HEA), 0.1 parts by mass of 1,6-hexanediol diacrylate (trade name "NK ESTER A-HD-N", manufactured by Shin-Nakamura Chemical Co., Ltd.), 2.0 parts by mass of an ultraviolet absorber (trade name "Tinosorb S", manufactured by BASF), and 0.3 parts by mass of a photopolymerization initiator (trade name "Omnirad 819", manufactured by IGM Resins BV) were added and mixed to obtain an adhesive composition (pre-cured composition).
[0190] The adhesive composition was coated on a polyethylene terephthalate (PET) release liner (first release liner, trade name "MRF75", manufactured by Mitsubishi Chemical Corporation) so that the final thickness (thickness of the adhesive layer) was 100 μm, thereby forming a coating layer (adhesive composition layer). Next, a PET release liner (second release liner, trade name "MRE75", manufactured by Mitsubishi Chemical Corporation) was provided on the coating layer to cover the coating layer and block oxygen. Then, a laminate of MRF75 / coating layer (adhesive composition layer) / MRE75 was obtained.
[0191] Next, the laminate was irradiated with a black light (manufactured by Toshiba Corporation) from the upper surface (MRF75 side) of the laminate at an illuminance of 5 mW / cm 2 The mixture was irradiated with ultraviolet light for 300 seconds. Then, it was dried in a 90° C. dryer for 2 minutes. Then, a substrate-free double-sided PSA sheet consisting of only the PSA layer and protected on both sides of the PSA layer by release liners was obtained.
[0192] [Example 2, Comparative Examples 1, 2]
[0193] A substrate-free double-sided PSA sheet was obtained in the same manner as in Example 1 except that the composition of the PSA composition was changed to that shown in Table 1. In addition, the unit of the numerical values in Table 1 represents [parts by mass] unless otherwise specified.
[0194] The details of the components shown in Table 1 are as follows.
[0195] HEA: 2-Hydroxyethyl Acrylate
[0196] 1,6-HD: 1,6-Hexanediol diacrylate
[0197] ISTA: Isostearyl acrylate
[0198] TMPTA: Trimethylolpropane triacrylate
[0199] BI-3000: Trade name "BI-3000", hydrogenated 1,2-polybutadiene, number average molecular weight (Mn): 2930 (measured value), weight average molecular weight (Mw): 4050 (measured value), polydispersity (Mw / Mn): 1.38 (measured value), hydrogenation rate: 97% or more (product catalog value), iodine value: 21 or less (product catalog value), manufactured by Nippon Soda Co., Ltd.
[0200] GI-2000: Trade name "GI-2000", hydrogenated 1,2-polybutadiene diol, number average molecular weight (Mn): 3110 (measured value), weight average molecular weight (Mw): 5090 (measured value), polydispersity (Mw / Mn): 1.64 (measured value), hydrogenation rate: 97% or more (product catalog value), iodine value: 21 or less (product catalog value), manufactured by Nippon Soda Co., Ltd.
[0201] Tinosorb S: UV absorber, trade name "Tinosorb S", manufactured by BASF
[0202] Omnirad 819: Photopolymerization initiator, trade name "Omnirad 819", manufactured by IGM Resins BV
[0203] The measured values of the number average molecular weight (Mn), weight average molecular weight (Mw) and polydispersity (Mw / Mn) of the hydrogenated polyolefin and the hydrogenated polyolefin polyol are values obtained from values calculated by polystyrene conversion after measurement by gel permeation chromatography (GPC) under the following conditions.
[0204] Analytical device: GPC: HLC-8320GPC (Tosoh)
[0205] Determination conditions:
[0206] Column: TSKgel SuperHZM-H / HZ4000 / HZ3000 / HZ2000
[0207] Column size: 6.0mm inner diameter x 150mm
[0208] Eluent: THF (tetrahydrofuran)
[0209] Flow rate: 0.6mL / min
[0210] Detector: Differential Refractometer (RI)
[0211] Column temperature: 40°C
[0212] Injection volume: 20 μL
[0213] [evaluate]
[0214] The following evaluations were performed on the substrate-less double-sided PSA sheet. The results are shown in Table 1.
[0215] (1) Dielectric constant (Dk)
[0216] The adhesive layer obtained by peeling off the release liner from the substrate-free double-sided adhesive sheet obtained in the example or comparative example was sandwiched between a copper foil and an electrode, and the dielectric constant at a frequency of 100 kHz was measured using the following apparatus. For the measurement, three samples were prepared, and the average value of the measured values of these three samples was taken as the dielectric constant.
[0217] In addition, the dielectric constant of the adhesive layer at a frequency of 100 kHz was measured under the following conditions in accordance with JIS K6911.
[0218] Measurement method: Capacitance method (device: Agilent Technologies 4294A Precision Impedance Analyzer)
[0219] Electrode structure: 12.1mmφ, 0.5mm thick aluminum plate
[0220] Counter electrode: 3oz copper plate
[0221] Measurement environment: 23℃±1℃, 52%±1%RH
[0222] (2) Glass Adhesion
[0223] The substrate-free double-sided adhesive sheet obtained in the embodiment or comparative example was cut into a size of 20 mm in width and 80 mm in length to prepare a measurement sample. Under an environment of 23°C and 50% RH, the adhesive layer of the above-mentioned measurement sample was exposed, and the adhesive layer was attached to a glass plate (thickness 0.7 mm), and was subjected to autoclave treatment at 50°C and 0.5 MPa for 15 minutes to make it close. Under an environment of 23°C and 50% RH, a tensile tester was used to measure the glass adhesion (10N / 20mm) under the conditions of a peeling angle of 180 degrees and a pulling speed of 300 mm / min. As a tensile tester, a universal tensile compression tester (device name "tensile compression tester, TCM-1kNB", manufactured by Minebea Corporation) was used. It should be noted that during the measurement, appropriate lining materials can be attached to the adhesive tape as the measurement object for reinforcement as needed (for example, when the substrate is easily deformed). As a lining material, for example, a PET film with a thickness of about 50 μm can be used, and the lining material is used in the embodiments and comparative examples described in this specification.
[0224] (3) Glass transition temperature (Tg)
[0225] The glass transition temperature (Tg) of the substrate-free double-sided PSA sheet obtained in the examples or comparative examples was calculated using the above-mentioned Fox equation.
[0226] (4) Dielectric loss tangent
[0227] For the substrate-free double-sided PSA sheets obtained in the examples or comparative examples, except that the frequency was set to 10 3 Hz~10 4 Except for Hz, the dielectric loss tangent was measured by the same method as the above-mentioned dielectric constant.
[0228] (5) Rework
[0229] The substrate-free double-sided adhesive sheet obtained in the example or comparative example was subjected to the same treatment as the above-mentioned glass adhesion measurement. The sample was peeled off from the glass plate by hand, and the reworkability was evaluated according to the following criteria. Regarding the evaluation of reworkability, three samples were prepared according to the above-mentioned steps and the process was repeated three times.
[0230] ○: Among the three samples, a part of the sheets was broken, but the sheets were peeled off again.
[0231] △: All three samples were broken, but the samples were peeled off again.
[0232] ×: All three samples had adhesive residue or the film broke and could not be peeled off even after peeling several times.
[0233] (6) Drop impact resistance
[0234] (Preparation of evaluation samples)
[0235] The substrate-free double-sided adhesive sheet obtained in the embodiment or comparative example is cut into a length of 75mm×width 45mm, and the second release liner is peeled off from the above-mentioned adhesive sheet, and the exposed adhesive sheet is bonded to the center of the first glass plate (length 100mm×width 75mm, thickness 500μm) along the four sides. A roller laminator is used for bonding, and the pressure between the rollers is 0.2MPa and the conveying speed is 100mm / minute. Next, the first release liner is peeled off from the adhesive sheet on the first glass plate, and the exposed adhesive layer is bonded to the center of the second glass plate (length 100mm×width 50mm, thickness 500μm) with a printed layer along the four sides, thereby obtaining a joint body. The printed layer (thickness 30μm, black ink layer) is formed on one side of the thickness direction of the second glass plate in a range of 15mm from each end to the inside, and in the width direction, it is formed in a range of 5mm from each end to the inside of the first glass plate. The adhesive layer is bonded to the center of one side of the thickness direction of such a second glass plate, and the entire edge of the adhesive layer is in contact with the above-mentioned printed layer. That is, the printed layer on the second glass plate was sandwiched between the second glass plate and the adhesive layer within a range of 2.5 mm from the inner end of the printed layer to the outer side. Such a bonded body was heat treated at 50° C. and 0.5 MPa for 30 minutes to prepare an evaluation sample.
[0236] The following drop impact resistance test was performed on the evaluation samples.
[0237] The evaluation sample is placed on a support table in such a manner that the first glass plate in the evaluation sample is located on the upper side, the two ends of the first glass plate in the width direction are supported by the support table from below, and the second glass plate below does not contact the support table. Next, the evaluation sample on the support table is fixed to the support table using an adhesive tape. Next, the support table and the evaluation sample are kept at -5°C for 24 hours. The support table and the evaluation sample are restored to room temperature, and then a metal ball is dropped onto the evaluation sample on the support table within 40 seconds so that the metal ball collides with the first glass plate of the evaluation sample. The mass of the metal ball is 15g. In addition, the falling position of the metal ball relative to the evaluation sample is a position separated from the printed layer by 10mm in the length direction and the width direction respectively. Two tests (tests using different samples) (n=2) are performed on each adhesive sheet. The falling height of the metal ball in the first test is 300mm, and the falling height of the metal ball in the second test is 400mm. Then, regarding the drop impact resistance of the pressure-sensitive adhesive sheet, the case where no peeling of the pressure-sensitive adhesive layer occurred in the first and second tests was evaluated as "excellent", the case where no peeling occurred only in the first test was evaluated as "acceptable", and the case where peeling occurred in both the first and second tests was evaluated as "poor".
[0238] Table 1
[0239] Example 1 Example 2 Comparative Example 1 Comparative Example 2 Polymer A 100 100 100 Polymer B 100 HEA 20 20 20 1,6-HD 0.1 0.1 0.1 ISTA 80 80 TMPTA 0.15 BI-3000 5 GI-2000 15 Tinosorb S 2 2 1 Omnirad 819 0.3 0.3 0.2 Dk(100KHz) 3.2 3.2 4.3 2.7 Glass adhesion (N / 20mm) 19.8 14.2 10.6 16.6 Tg(℃) -3 -3 -7 -3 <![CDATA[Dielectric loss tangent (10 3 Hz to 10 4 Hz)]]> 1.53~1.07 1.54~1.17 1.53~0.93 1.27~0.71 Rework ○ ○ △ ○ Drop impact resistance qualified excellent qualified bad
[0240] It was confirmed that the adhesive sheet disclosed in the examples has a sufficiently low dielectric constant, reduces noise generation, has sufficient glass adhesion, is easily attached to an adherend, and exhibits drop impact resistance (Example 1, Example 2). On the other hand, when the Tg of the acrylic polymer is low, although it has drop impact resistance, it cannot achieve a low dielectric constant (Comparative Example 1), and when the dielectric loss tangent in the high-speed region is small, although the dielectric constant is low, it cannot exhibit drop impact resistance (Comparative Example 2).
Claims
1. An adhesive sheet, wherein: The adhesive sheet comprises an adhesive layer, The adhesive layer does not peel off in the following drop impact resistance test, The dielectric constant of the adhesive layer at a frequency of 100 kHz is 4 or less, At least one surface of the adhesive layer has a glass adhesive strength of 10 N or more / 20 mm under the conditions of a peeling angle of 180° and a pulling speed of 300 mm / min, The adhesive sheet is used for an optical member. <Drop impact resistance test> A first glass plate (length 100 mm × width 75 mm, thickness 500 μm), the adhesive layer (length 75 mm × width 45 mm), a printed layer (thickness 30 μm) formed within a range of 15 mm inside the entire end edge of the second glass plate, and the second glass plate (length 100 mm × width 50 mm, thickness 500 μm) are stacked in sequence, and heat treated at 50°C, 0.5 MPa, and 30 minutes to produce a joint body; in a state where only the protrusions at both ends of the first glass plate in the width direction are supported by a support platform and the second glass plate is not in contact with the support platform, the joint body is set on a support platform in a manner such that the first glass plate is located on the upper side of the joint body, a metal ball with a mass of 15 g is dropped from a height of 300 mm toward the first glass plate, and it is confirmed whether there is peeling between the adhesive layer and the first glass plate or between the adhesive layer and the printed layer at this time.
2. The adhesive sheet according to claim 1, wherein After the drop impact resistance test, the adhesive layer did not peel even when left at 80° C. for one week.
3. An optical member with an adhesive layer, wherein: The pressure-sensitive adhesive sheet according to claim 1 or 2 is bonded to at least one surface of an optical member.
4. An image display device, wherein: The image display device comprises the pressure-sensitive adhesive layer-attached optical member according to claim 3 .
5. The image display device according to claim 4, wherein: The image display device is a touch panel.
